Pengaruh Employee Engagement, Quality Of Work Life, dan Kepercayaan pada Pimpinan terhadap Organizational Citizenship Behaviour - boris stefen; H.M Hermansyur; Bunga Aditi (JaManKu: Jurnal Manajemen dan Kewirausahaan, 2020)
The main objective of this research is to clarify the influence of Employee Engagement, Quality of Work Life, and Leader Trust to Organizational Citizenship Behaviour in PT Jiwasraya Insurance on Medan. The population in this study were all employees working, amounting to 140 people with samples taken by 100 people. This type of research is associative research. Methods of collecting data in this study were questionnaires and interviews. The research method used in this study is multiple linear regression analysis. Based on the results obtained, H1 is accepted for the Employee Engagement variable with alpha 1%. Thus, partially that the Employee Engagement variable has a significant effect on Organizational Citizenship Behavior, H2 is rejected for the Quality of Work Life variable. Thus, partially that the Quality of Work Life variable does not have a significant effect on Organizational Citizenship Behavior, H3 is rejected for the Trust variable in the Leader. Thus, partially that the variable Trust in leadership does not have a significant effect on Organizational Citizenship Behavior, It concluded that H4 simultaneous Employee Engagement, Quality of Work Life, and Trust in Leaders do not have a significant effect on Organizational Citizenship Behavior at PT. Jiwasraya Insurance (Persero) Medan.